(untitled) (GEON Journal (Management, Organizations and Business), 2020)
The work of human management is to achieve the generation of value in organizations, for this it must contribute to mediation between management and collaborators, it is necessary that each do their part, since it must be a teamwork with synergy that achieves contribute to the achievement of organizational goals so that all interest groups walk towards the same specific objectives, effective organizational development